A preview of digital ecosystem & engagement through gaming in the context of Bangladesh, Robi Axiata Ltd - Mahbub, Samiya Tanvie (Brac University, 2020)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2020.